Recent Advances in the Total Synthesis of Clavaminols - Jin, Tian; Zhao, Lu; Liu, Xiao; Sun, Liang; Lin, Jia-Fu; Zheng, Zhe-Bin (Synthesis, 2018)
Clavaminols are a new class of long-chain 2-amino-3-alkanols that mostly contain 2R,3S-configurations. Owing to their interesting molecular architectures and promising activities, they have become popular targets for synthetic organic chemists. In this review, we highlight 12 total syntheses of clavaminols from different research groups during the period 2009 to 2018.1 Introduction2 Synthetic Approaches toward Clavaminols2.1 Total Synthesis by Chemla and Colleagues (2009)2.2 Total Synthesis by Greck and Colleagues (2010)2.3 Total Synthesis by Sutherland and Zaed (2011)2.4 Total Synthesis by Huang and Colleagues (2011)2.5 Total Synthesis by Kotora and Colleagues (2012)2.6 Total Synthesis by Kumar and Colleagues (2013)2.7 Total Synthesis by Prabhavathi Devi and Colleagues (2013 and 2016)2.8 Total Synthesis by Sarabia and Colleagues (2014)2.9 Total Synthesis by Mohapatra and Colleagues (2016)2.10 Total Synthesis by Lu and Colleagues (2016)2.11 Total Synthesis by Jin and Colleagues (2017)2.12 Total Synthesis by Kumar Pandey and Colleagues (2018)3 Conclusion
Keywords: total synthesis; clavaminols; natural products; long-chain 2-amino-3-alkanols; antitumor activity